J.K. Kloppers, D. Nakare and L.M. Isala (Compilers), A.W. Bredell (Editor). Bukenkango Rukwangali-English. English-Rukwangali Dictionary. - Legère, Karsten (Lexikos, 1995)
Review of J.K. Kloppers, D. Nakare and L.M. Isala (Compilers), A.W. Bredell (Editor). Bukenkango Rukwangali-English. English-Rukwangali Dictionary.